Technologies for African Agricultural Transformation (TAAT) celebrates 143 interventions in 132 sites across Africa: Updates 2018, Issue 001 - Technologies for African Agricultural Transformation (Technologies for African Agricultural Transformation, 2018)
The Technologies for African Agricultural Transformation (TAAT) Program was initiated by the African Development Bank (AfDB) as part of its Feed Africa Initiative. TAAT’s main objective is to improve the business of agriculture across Africa by raising agricultural productivity, mitigating risks, and promoting diversification and processing in 18 agricultural value chains within eight Priority Intervention Areas (PIA).